A comparative analysis of island floras challenges taxonomy‐based biogeographical models of speciation. (16th January 2015) - Igea, Javier; Bogarín, Diego; Papadopulos, Alexander S. T.; Savolainen, Vincent
<x xml:space="preserve">Abstract</x> Speciation on islands, and particularly the divergence of species in situ, has long been debated. Here, we present one of the first, complete assessments of the geographic modes of speciation for the flora of a small oceanic island. Cocos Island (Costa Rica) is pristine; it is located 550 km off the Pacific coast of Central America. It harbors 189 native plant species, 33 of which are endemic. Using phylogenetic data from insular and mainland congeneric species, we show that all of the endemic species are derived from independent colonization events rather than in situ speciation. This is in sharp contrast to the results of a study carried out in a comparable system, Lord Howe Island (Australia), where as much as 8.2% of the plant species were the product of sympatric speciation. Differences in physiography and age between the islands may be responsible for the contrasting patterns of speciation observed. Importantly, comparing phylogenetic assessments of the modes of speciation with taxonomy‐based measures shows that widely used island biogeography approaches overestimate rates of in situ speciation.